ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA MEDIA PERS ONLINE PADA KASUS PENCEMARAN NAMA BAIK (STUDI PUTUSAN NOMOR 36/Pid.B/2015/PN Lrt) - Novatika, Fajria; Riyanto, Agus (LPPM Universitas Putera Batam, 2019)
Media press are vulnerable to defamation cases, as happened in decision No.36/Pid.B/2015/PN.Lrt. From this decision a research will be conducted on how the criminal responsibility of the online press media bridges the occurrence of criminal acts of defamation and to find out how the judge judges the basis for giving a verdict. Normative Legal Research Methods used. The results of the research that the press must be responsible for the news published because in the news, there are often cases of defamation which result in criminal acts and results and in the judgment of judges in determining actions taken by public prosecutors based on article 310 paragraph (1) of the Criminal Code Jo Article 84 Paragraph (2) Law No.8 of 1981, Article 310 Paragraph (2) of Criminal Code Article 84 Paragraph (2) of Law No.8 of 1981, Article 311 Paragraph (1) of Criminal Code Article Jo Paragraph (2) of Law No. 8 of 1981. From research on the pattern of relations that must be held as a handle between the press, the public, and the government is a free and responsible press, and in making decisions on all aspects in it, accuracy, law, reasoning, mastery of material and formal problems.